Interaksi Dengan Al-Qur’an Melalui Metode Tafsir Tematik Perspektif Yusuf Al-Qardhawi - Humaidi; Iqbal Kholidi (Al-Qadim: Jurnal Tafsir dan Ilmu Tafsir, 2024)
Thematic interpretation of the Qur'an is a method of interpretation that involves collecting verses from the Qur'an related to a particular theme. This approach is becoming increasingly important in dealing with the difficulties faced by society today. In the era of information and globalization, interpretation of the themes of the Koran can provide solutions to problems that are developing in various parts of the world. The thematic interpretation method can also be prepared practically and systematically by following the chronology of the revelation of the verses, so that it can keep up with the times by adapting to all places, situations and conditions. One of the figures who provides ideas and solution techniques in understanding the text of Al- Qur'an is Yusuf al-Qardhawi. He emphasized the importance of gaining a good and thorough understanding by avoiding narrow and unfounded textual interpretations. This article is a literature study that focuses on al-Qardhawi's method in understanding the text of the Qur'an. The thematic interpretation approach introduced by al-Qardhawi allows readers of the Qur'an to understand the messages of the Qur'an more broadly and are relevant to the contemporary context.